MAXIMUM TRANSGRESSIONS IN THE LOVING RELATIONS BETWEEN BLACK AND BLACK SLAVES IN THE NEW KINGDOM OF GRANADA DURING THE HISPANIC DOMAIN PERIOD - Pita Pico, Roger (Revista de Historia Social y de las Mentalidades, 2024)
In the time of the old Spanish regime, the love relations between white and black slave were marked by the repression derived from the closed and hierarchical social structure of that time. The present article tries to address the maximum transgressions that occurred in this type of ties in the New Kingdom of Granada, such as: marriage attempts, rape, the challenge of priests, bonds between slaves and the children of their masters and love affairs between white women and slaves, cases that under the mentality of the time were described as a maximum breach of the social order and Christian morality, being of course the object of greater censorship and public pointing.